Opportunistic and playback-sensitive scheduling for video streaming - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan (Academy & Industry Research Collaboration Center (AIRCC), 2014)
Given the strict Quality of Service (QoS) requirements of video streaming, this paper proposes a novel solution for simultaneous streaming of multiple video sessions over a mobile cellular system. The proposed solution combines a buffer management strategy with a packet scheduling algorithm. The buffer management strategy selectively discards packets of a user from base station buffer whereas the packet scheduling algorithm schedules packets of a user according to its instantaneous channel quality, average throughput and playback buffer information. Simulation results demonstrate that the proposed solution is effective in providing a continuous video playback with good perceptual quality for more users. If at least a good perceptual quality is to be satisfied for all users (QoS constraint of video streaming), then the proposed solution improves the system capacity by 40% over a conventional packet scheduling algorithm.